Composition, additive, and process engineering of halide perovskite green photodetector for enhanced responsivity and detectivity - Jo, Bonghyun; Cho, In Sun; Kim, Kyung Min; Sohn, Chang hoon; Kim, Jihyun; Kang, Joohoon; Han, Gill Sang; Jung, Hyun Suk (Journal of Alloys and Compounds, 2023)
Si-based materials have been successfully adapted for photodiode (PD) sensing applications. However, their micrometer-scale thickness requirement and parasitic light absorption limit color discrimination. In this study, we developed halide-perovskite-based thin films through composition engineering and process optimization for green-light sensing with high detectivity and responsivity. First, composition engineering studies, i.e., ratio control of methylammonium (MA) and formamidinium (FA) precursors and subsequent annealing condition optimization, were conducted to control the bandgap and phase formation of green-targeted perovskite absorber films. Next, we studied the effect of the CH3NH3Cl (MACl) additive on reducing the dark current and enhancing phase stability. Notably, space-charge-limited current measurements revealed that MACl could effectively reduce the trap density. Furthermore, simultaneous optimization of the cationic site composition, annealing conditions, and additive significantly affected the perovskite film morphology, phase stability, and defect formation, enabling the fabrication of high-performance green PDs. Our optimized, green-targeted PD exhibits a superior responsivity of 55.24 A·W−1 (under 7.17 × 10−7 W·cm−2 excitation), an average external quantum efficiency of 86%, and a high on/off ratio, thereby providing a feasible approach for future PD commercialization.
Keywords: Additive engineering; Annealing condition; Composition engineering; Detectivity; Green photodetector; Halide perovskites; Mixed halide perovskite; Process optimisation; Responsivity; Si-based materials; Additive engineering; Composition engineering; Green photodetector; Mixed halide perovskites; Process optimization